Crystal structures of two 6-(2-hydroxybenzoyl)-5H-thiazolo[3,2-a]pyrimidin-5-ones - Gomes, Ligia R. (2015)
he title compounds, 6-(2-hydroxybenzyl)-5H-thiazolo[3,2-a]pyrimidin-5-one, C13H8N2O3S, (1), and 6-(2-hydroxybenzyl)-3-methyl-5H-thiazolo[3,2-a]pyrimidin-5-one, C14H10N2O3S, (2), were synthesized when a chromone-3-carboxylic acid, activated with (benzotriazol-1-yloxy)tripyrrolidinylphosphonium hexafluoridophosphate (PyBOP), was reacted with a primary heteromamine. Instead of the expected amidation, the unusual title thiazolopyrimidine-5-one derivatives were obtained serendipitously and a mechanism of formation is proposed. Both compounds present an intramolecular O-H...O hydrogen bond, which generates an S(6) ring. The dihedral angles between the heterocyclic moiety and the 2-hydroxybenzoyl ring are 55.22 (5) and 46.83 (6)° for (1) and (2), respectively. In the crystals, the molecules are linked by weak C-H...O hydrogen bonds and [pi]-[pi] stacking interactions.